2016
DOI: 10.3329/bjsir.v51i2.28090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the adsorption kinetics of Cr(VI) on sodium chlorite treated coconut coir

Abstract: Coconut coir is a low cost bioadsorbent containing large amount of lignin. In this research work sodium chlorite treated coconut coir (SCT-CC) was used to remove Cr(VI) from industrial wastewater by implementing adsorption technique through the investigation of the adsorption kinetics at different pH values. The maximum Cr(VI) adsorption capacity of SCT-CC at pH 2.00, 3.00, 5.00 and 7.00 was 24.75, 23.92, 16.07 and 6.31 mg Cr(VI) g -1 SCT-CC respectively with the dose of 7.5 g/L. The equilibrium established wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The sodium chlorite method has shown promising results to reduce moisture content and to enhance the hydrophobic properties of the fiber. Sodium chlorite is utilized in bleaching the fibers to form chlorine dioxide, which reacts with lignin to effectively remove it, and also reacts with hemicellulose to improve the hydrophobic nature [ 120 , 121 ]. Steric acid contains carboxyl groups, and these groups react with hydroxyl groups to decrease their hydrophilic nature.…”
Section: Fiber Modificationmentioning
confidence: 99%
“…The sodium chlorite method has shown promising results to reduce moisture content and to enhance the hydrophobic properties of the fiber. Sodium chlorite is utilized in bleaching the fibers to form chlorine dioxide, which reacts with lignin to effectively remove it, and also reacts with hemicellulose to improve the hydrophobic nature [ 120 , 121 ]. Steric acid contains carboxyl groups, and these groups react with hydroxyl groups to decrease their hydrophilic nature.…”
Section: Fiber Modificationmentioning
confidence: 99%
“…However, further investigations must be achieved to explore the behaviour of affinity series and sorbent selectivity under the pH effect. In the affinity series of systems with single metal, this metal with the highest affinity may rarely be affected by the existence of other heavy metals in solution [40,41].…”
Section: (19)mentioning
confidence: 99%
“…The Cr(VI) adsorption efficiency of activated carbon based on coconut shell was reported to decrease with the increase of the system pH values from 2 to 10. Islam et al (2016) showed the effect of pH on the adsorption kinetics of Cr(VI) on sodium chlorite treated coconut coir. In that case the rate of adsorption was shown to decrease as the pH was tuned from lower to higher values.…”
Section: Effect Of Phmentioning
confidence: 99%